2005
DOI: 10.1590/s1413-70542005000300012
|View full text |Cite
|
Sign up to set email alerts
|

Potencial da região sul de Minas Gerais para a produção de cafés especiais (I - Atividade da polifenoloxidase, condutividade elétrica e lixiviação de potássio)

Abstract: A qualidade do café está diretamente relacionada com a composição química dos grãos. Neste contexto, o objetivou-se com o presente trabalho realizar uma avaliação química em amostras de café de 22 municípios da região Sul de Minas Gerais, selecionados por apresentarem uma população cafeeira superior a dez milhões de pés. Foram coletadas amostras de café em dez propriedades de cada município, totalizando 220 amostras. Após serem beneficiadas, as amostras foram analisadas quanto às características químicas de at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this case, the Lavras environment, when combined with Catigua MG2 and Araponga MG1 cultivars, stands out for the production of specialty coffees. According to results demonstrated presented by Chagas, Malta and Pereira [19] based on data from 22 cities, the southern region of Minas Gerais has favorable soil and climatic characteristics for the production of top quality coffees.…”
Section: Meanmentioning
confidence: 96%
“…In this case, the Lavras environment, when combined with Catigua MG2 and Araponga MG1 cultivars, stands out for the production of specialty coffees. According to results demonstrated presented by Chagas, Malta and Pereira [19] based on data from 22 cities, the southern region of Minas Gerais has favorable soil and climatic characteristics for the production of top quality coffees.…”
Section: Meanmentioning
confidence: 96%
“…Our results showed that the post-harvest practices applied to the samples were efficient for the expression of sensory quality. In addition to the genetic aspects of the cultivars and post-harvest processing, the region chosen for this experiment, Southern Minas Gerais, was considered adequate according to Chagas et al (2005). These authors analyzed 22 counties in the southern region of Minas Gerais and concluded that this region has favorable soil and climate characteristics for producing superior quality coffee.…”
Section: Discussionmentioning
confidence: 99%